A Bioinspired Versatile Spore Coat Nanomaterial for Oral Probiotics Delivery. (17th July 2021) - Song, Qingling; Zhao, Hongjuan; Zheng, Cuixia; Wang, Ke; Gao, Hui; Feng, Qianhua; Zhang, Hongling; Zhang, Zhenzhong; Zhang, Yun; Wang, Lei
Abstract: A fundamental challenge in probiotic therapy is effective delivery and rapid colonization of probiotics; however, the physiological structure of probiotic spores provides an interesting idea to address this problem. Herein, the spore coat is innovatively prepared into a type of versatile spore coat nanomaterial (CN) which is subsequently anchored to the surface of probiotics to form CN‐coated probiotics. The CN retains the characteristics of high resistance and natural affinity of spore coats, which serve as the "armor" for the enhancement of the probiotics delivery. Moreover, CN is beneficial for the explosive proliferation and competitive colonization of probiotics. Notably, it is found that not only CN used solely has good anti‐inflammatory effect, but also it can significantly improve the functions of probiotics such as microbiome regulation, gut barrier integrity and tumor prevention. This work provides a simple and universal strategy that may guide the development of nanomaterial and material‐based microecological agents. Abstract : A spore coat nanomaterial (CN) with properties of high tolerance, anti‐inflammatory, natural affinity, etc. is prepared from probiotic spores. Intrigued by these promising characteristics of CN, a series of microecological agents is further developed by anchoring the CN to the surface of probiotics. This study provides a universal strategy for developing the biomaterials and delivering the probiotics for disease treatment.